Optimism and Academic Resilience Correlate with Student Subjective Well-Being: Optimisme dan Ketahanan Akademik Berkorelasi dengan Kesejahteraan Subjektif Mahasiswa - Chafi Rozyi Putri Maulidhah; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Subjective well-being reflects overall life satisfaction accompanied by frequent positive emotions and minimal negative emotions, representing a crucial indicator of psychological functioning among adolescents. Specific Background: In the school context, students often face academic stressors, including examination anxiety, learning difficulties, and uncertainty about future plans, which are associated with reduced psychological comfort and happiness. Knowledge Gap: Previous studies have separately examined psychological predictors of subjective well-being; however, limited research integrates optimism and academic resilience simultaneously among Indonesian high school populations. Aims: This study aimed to examine the relationship between optimism and academic resilience with subjective well-being among students at SMA Negeri 1 Krian. Results: Using a quantitative correlational design with 275 students, Pearson Product Moment analysis revealed significant positive relationships between optimism and subjective well-being (r = 0.592, p < .001) and between academic resilience and subjective well-being (r = 0.557, p < .001). Multiple linear correlation indicated that both predictors jointly accounted for 38.3% of the variance in subjective well-being. Novelty: This study integrates two psychological and academic predictors within a single correlational model focusing on Indonesian senior high school students. Implications: The findings highlight the importance of fostering positive future expectations and adaptive coping capacities to support students’ psychological satisfaction and emotional stability within academic environments, providing insights for school-based developmental and counseling programs. Highlights: Positive Pearson Coefficients Demonstrated Significant Associations Between Psychological Outlook, Learning Adaptability, and Life Satisfaction Indicators. Combined Predictors Explained 38.3% Variance in Adolescent Psychological Satisfaction Scores. Higher Positive Future Expectations and Adaptive Coping Tendencies Accompanied Greater Emotional Balance in School Environments. Keywords: Subjective Well-Being, Optimism, Academic Resilience, High School Students, Correlational Study